Plasma and cerebrospinal fluid pharmacokinetics of hydroxysafflor yellow A in patients with traumatic brain injury after intravenous administration of Xuebijing using LC-MS/MS method. (3rd May 2020) - Sheng, Chenxia; Peng, Weijun; Xia, Zian; Wang, Yang
Abstract: Hydroxysafflor yellow A (HSYA) is the most pharmaceutically relevant compound in Xuebijing (XBJ) for traumatic brain injury (TBI) treatment. We aimed to investigate biofluids pharmacokinetics of HSYA from XBJ to ensure the drug safety and to guide the clinical use. A sensitive, rapid and reliable liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was applied to investigate pharmacokinetics of HSYA in TBI patients after intravenous administration of XBJ. Non-compartmental methods using DAS 3.0 software were applied to analyse the pharmacokinetic parameters. A similar half-life (Plasma t 1/2 : 14.55 ± 3.51 h vs. CSF t 1/2 : 15.73 ± 3.63) was observed. HSYA reached the peak level rapidly, but exhibited a strongly slow absorption phase from blood to cerebrospinal fluid (CSF, Plasma Tmax : 0.69 ± 0.26 h vs. CSF Tmax : 4.0 ± 2.62 h). HSYA exhibited much higher Cmax (Plasma Cmax : 9342.76 ± 2489.23 μg/L vs. CSF Cmax : 98.08 ± 14.51 μg/L) and AUC0-t (Plasma AUC0-t : 57490.5 ± 5560.3 μg h/L vs. CSF AUC0-t : 1851.6 ± 269.1 μg h/L), yet a shorter CL (Plasma CL : 0.02 ± 0.002 L/h/kg vs. CSF CL : 0.55 ± 0.01 L/h/kg) in plasma than in CSF. The AUC CSF / AUC plasma of HSYA was almost 3.37%. In summary, the results demonstrate that part of HSYA come across blood-brain barrier after XBJ administration. This study provides evidence for better understanding the pharmacokinetics and potential for clinical guidance of XBJ for TBI treatment.